Hubungan Usia Dan Status Gizi Ibu Hamil Dengan Kejadian Berat Badan Lahir Rendah - Endartiwi, Sri Sularsih; Elang Fajri Ma’rifah (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Low birth weight (LBW) is a condition of the baby who was born less than 2.500 gr regardless of prenancy period. Low birth weight (LBW) are the main problem that contributes perinatal mordibitas rate and perinatal mortality rate. Incidence of low birth weight (LBW) in the Bantul regency are the work area Kasihan I Health Center that found 69 cases. Based on the results of the preliminary study at Kasihan I Health Center, the age of pregnant women and the nutritional status of pregnant women is both factors that contribute to incidence of low birth weight (LBW) at Kasihan I Health Center. This research is to know the correlation between age of pregnant women and nutritional status of pregnant women with incidence of low birth weight in Kasihan I Health Center in 2022. This type of research is analytical observasion with case control design research. The population of this study were all mothers who gave birth to Kasihan I health center in 2020 as many as 36 people. Samples were taken using a saturated sampling of 32 people. The data analysis used is univariate and bivariate analysis. Based on the chi square statistical test, p-value = 0,815 ( p > 0,05), the result show that there was no correlation between age of pregnant women with incidence of low birth weight (LBW), and p-value = 0,014 ( p < 0,05), there was correlation between nutritional status of pregnant women with incidence of low birth weight (LBW). There was no correlation between age of pregnant women with incidence of low birth weight in Kasihan I Health Center in 2022. There was correlation between nutritional status of pregnant women with incidence of low birth weight. Pregnant women can get a nutritional status checking in health facility to prevent LBW